Epidemiological Profile of Anaemia Among Rural School Going Adolescents of District Bareilly, India - Ajay Kumar Agarwal; Hari Shankar Joshi; Syed Esam Mahmood; Arun Singh; Mahendra Sharma (Medsci Publications, 2015)
Background: WHO estimates that India has highest prevalence of anaemia among the South East Asian Countries. During adolescence anaemia is more prevalent due to growth spurt. Objectives: To find out the prevalence of anaemia among rural school going adolescents and to identify the associated factors. Material and Methods: One year cross sectional study was con- ducted in western Uttar Pradesh among 900 school going adolescents using multistage sampling. A structured schedule was used to collect the information. Chi-square test was applied to analyse data using SPSS software. Results: The overall prevalence of anaemia was 58.67%. Prevalence of anaemia was significantly higher among the females (65.11%). Higher prevalence of anaemia was found among adolescents aged between 10-14 years (59.58%), Hindus (62.04%), middle socio- economic class (78.89%) and joint families (59.63%). Higher preva- lence was also found among those adolescents whose mothers and fathers were educated upto primary level (58.87% and 60.83% respectively). Conclusion: High prevalence of anaemia was found, especially among the female adolescents. Adequate food consumption and reg- ular intake of iron and vitamin C rich foods during early childhood period, de-worming, food fortification, supplementary feeding and nutrition education of parents can prevent nutritional anaemia in adolescents.